Jet-Breaking Extrusion of Alginate–Chitosan Capsules for Encapsulation of Plant Growth–Promoting Extremophilic Fungi - César Arriagada-Escamilla; Javier Ortiz; Nicole Iturra; Javiera Soto; Eduardo Morales (Microorganisms)
Drought and metal pollution severely impact plant growth. Root-associated extremophilic fungi can improve plant performance, and their encapsulation improves protection and effectiveness. This study optimized the encapsulation conditions for an extremophilic fungus with plant growth-promoting traits using alginate–chitosan capsules. An endophytic fungus was isolated from the roots of Neltuma chilensis from the Atacama Desert and identified via internal transcribed spacer (ITS) sequencing. Its plant growth-promoting traits, including exopolysaccharide, ammonium, siderophore, and indole acetic acid production and phosphorus solubilization, were evaluated. Freeze-dried Penicillium nalgiovense was encapsulated using jet-breaking extrusion, and capsule morphology and fungal survival were assessed via scanning electron microscope (SEM), confocal laser scanning microscopy (CLSM), and viability tests. Using Taguchi’s design, optimal conditions for sphericity (0.914 ± 0.002) and mean size (3.232 ± 0.087 mm) were achieved with 1% chitosan, a 5 cm distance to the gelation bath, and a 40 Hz vibration frequency. CLSM analysis confirmed the presence of the chitosan outer layer, revealing the capsule’s coating material encapsulating the fungus P. nalgiovense. The encapsulated fungus remained viable across disinfection times, demonstrating effective protection and gradual release. These findings emphasize the need for precise parameter control in fungal encapsulation, providing a basis for developing robust bioinoculants to support plant resilience in extreme environments.